2023
DOI: 10.1155/2023/8863318
|View full text |Cite
|
Sign up to set email alerts
|

CBCT Evaluation of Quality and Quantity of Bones for Immediate Implant Treatment Planning in Central Incisor Area in relation to Arch Form

Abstract: Understanding the quality of the ridge and facial cortical bone in the aesthetic zone is important for treatment with an immediate dental implant. This study aimed to analyze bone density and widths of the facial cortical bone and alveolar ridge at the central incisors in relation to arch form. A total of 400 teeth from 100 cone-beam CT images were divided equally between the upper and lower central incisors. The central incisor area was assessed for the width of the facial cortical and alveolar bones at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…17 Evaluation of substantial odontogenic and non-odontogenic cysts as well as benign jaw tumors may be facilitated by CBCT, may be used to help design the surgical approach by displaying the size of the lesion and its proximity to important structures, such as the maxillary sinus. 18,19 Also (56.5%) fourth year undergraduates and (43.5%) of interns agreed that CBCT can be used for cancer staging. This was in accordance to study conducted by the Sanger et al 17 which showed that majority of respondents agreed that CBCT can be used for cancer staging which is also consistent, with the following studies.…”
Section: Discussionmentioning
confidence: 99%
“…17 Evaluation of substantial odontogenic and non-odontogenic cysts as well as benign jaw tumors may be facilitated by CBCT, may be used to help design the surgical approach by displaying the size of the lesion and its proximity to important structures, such as the maxillary sinus. 18,19 Also (56.5%) fourth year undergraduates and (43.5%) of interns agreed that CBCT can be used for cancer staging. This was in accordance to study conducted by the Sanger et al 17 which showed that majority of respondents agreed that CBCT can be used for cancer staging which is also consistent, with the following studies.…”
Section: Discussionmentioning
confidence: 99%